Eight days in May : the final collapse of the Third Reich - Ullrich, Volker, 1943- (Liveright Publishing Corporation, a division of W. W. Norton & Company, 2021)
"The best-selling author of "Hitler: Ascent" and "Hitler: Downfall" reconstructs the chaotic, otherworldly last days of Nazi Germany. On April 30, 1945, in a bunker deep beneath the Old Reich Chancellery, Adolf Hitler and his newly wedded wife, Eva Braun, killed themselves. But Nazi Germany lived on, however briefly. The subsequent eight days were among the most turbulent in history, witnessing not only the final battles of World War II and the collapse of the Wehrmacht, but the near-total disintegration of the once-mighty Third Reich. In a taut, propulsive narrative, eminent historian Volker Ullrich depicts the final days of the Nazi empire through the eyes of Germans, both famous and ordinary, who experienced them. He takes us inside the phantomlike regime of Hitler's chosen successor, Admiral Karl Dönitz, while capturing the drama of a society in its death throes--from mass suicides to fanatics calling for one last stand. Integrating an astonishing variety of new primary sources, Ullrich offers an indispensable account of the costs of mass delusion"--